The year in tech 2023. - Harvard Business Review Press (Boston, Massachusetts : Harvard Business Review Press, 2023)
"From emotional AI and hybrid collaboration tools to crypto for business and no-code apps, tech innovations are reshaping organizations from the factory floor to the C-suite. What should you and your company be doing now to take advantage of the opportunities these technologies are creating-and to avoid falling victim to disruption? The Year in Tech, 2023: The Insights You Need from Harvard Business Review will help you understand what the latest and most important applications of new tech mean for your organization and how you can use them to compete and win in today's turbulent business environment. Business is changing. Will you adapt or be left behind?"--
Section 1. New fundamentals: How brands can enter the metaverse : build a strategy for the next frontier / by Janet Balis -- How NFTs create value : understanding this new asset class / by Steve Kaczynski and Scott Duke Kominers -- Stablecoins and the Future of Money : Will central banks and the private sector team up? / by Christian Catalini and Jai Massari -- The Future of Contactless Commerce : From "pay by face" to AI shopping assistants / by Mark Purdy -- How to Attract Top Tech Talent : New ways to recruit and retain in a competitive market / by Jonathan Frick, KC George, and Julie Coffman -- Section 2. Fresh Takes on Mature Tech: What Leaders Need to Know About the Cloud : What's next for your company's most efficient, innovative, and scalable platform? / by Bhaskar Ghosh and Karthik Narain -- Say Goodbye to Cookies : Demand personalization and privacy / by Tim Glomb -- Could Ransomware Attacks Ultimately Benefit Consumers? : When companies' own money is on the line, they take cybersecurity more seriously / by Rahul Telang -- Section 3. AI for the Rest of Us: AI Doesn't Have to Be Too Expensive or Complicated : Move your organization from a big-data approach to a good-data approach / by Andrew Ng -- No-Code Platforms Can Bring AI to Small and Midsize Businesses : Soon, anyone will be able to train an algorithm / by Jonathon Reilly -- How Warehouse Workers Really Feel About Automation : Employees from around the world share their hopes and concerns / by Joe Lui, Raghav Narsalay, Rushda Afzal, Ida Nair Sharma, and Dave Light -- Section 4. Trust Me: Do Your Digital Design Choices Take Advantage of Customers? : Misleading consumers into spending more can hurt you in the long run / by Michael Luca and Fiona Scott Morton -- How Digital Trust Varies Around the World : Attitudes, behaviors, environment, and user experience differ widely / by Bhaskar Chakravorti, Ajay Bhalla, and Ravi Shankar Chaturv
Includes index.
Description based on online resource; title from digital title page (viewed on November 11, 2022).
Added to collection customer.56279.3
Keywords: Business -- Technological innovations; Industrial management; Success in business; Business -- Technological innovations; Industrial management; Success in business